Why India Can Grow At 7 Percent a Year or More : Projections and Reflections - Rodrik, Dani.; Subramanian, Arvind (Washington, D.C. : International Monetary Fund, 2004)
Using a simple growth accounting framework, we project India's future potential output growth rate through 2025. We argue that there is perhaps more upside potential than downside risks to our central estimate of annual growth, which is close to 7 percent for aggregate output, or 5.5 percent for output per capita.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet